2015
DOI: 10.1126/science.aad0836
|View full text |Cite
|
Sign up to set email alerts
|

Sperm calcineurin inhibition prevents mouse fertility with implications for male contraceptive

Abstract: Calcineurin inhibitors, such as cyclosporine A and FK506, are used as immunosuppressant drugs, but their adverse effects on male reproductive function remain unclear. The testis expresses somatic calcineurin and a sperm-specific isoform that contains a catalytic subunit (PPP3CC) and a regulatory subunit (PPP3R2). We demonstrate herein that male mice lacking Ppp3cc or Ppp3r2 genes (knockout mice) are infertile, with reduced sperm motility owing to an inflexible midpiece. Treatment of mice with cyclosporine A or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
188
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 145 publications
(196 citation statements)
references
References 38 publications
7
188
1
Order By: Relevance
“…Despite diminished progressive movement, the sperm tails from null mice can beat; however, the range of flagellar beating is limited and appears to be asymmetric compared with that in wild type (Movies S1 and S2). Closer inspection of the sperm tails shows an inflexible midpiece (Movie S3) (30). The inflexible midpiece and asymmetric beating flagellum may account for the circular motion observed in KO sperm ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite diminished progressive movement, the sperm tails from null mice can beat; however, the range of flagellar beating is limited and appears to be asymmetric compared with that in wild type (Movies S1 and S2). Closer inspection of the sperm tails shows an inflexible midpiece (Movie S3) (30). The inflexible midpiece and asymmetric beating flagellum may account for the circular motion observed in KO sperm ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, without a preceding functional assay in vitro, many testis-enriched genes proved to be essential, by KO, for male reproduction. For example, TEX14 is required for intercellular bridge formation and progression through meiosis (7), GASZ functions in the piRNA pathway and is required for suppression of retrotransposons (8), CATSPER1 is a voltage-dependent calcium channel required for sperm hyperactivated motility (9), CLGN is an endoplasmic reticulum chaperone protein essential for sperm migration into the oviduct and fertilization (10), and PPP3R2 is a testis-specific regulatory subunit of calcineurin required for normal motility of the sperm midpiece (11). Taking these facts into account, it would be better to know first whether a gene of interest is essential in vivo before deciding to invest valuable research dollars and experimental time and personnel efforts into the project.…”
Section: Significancementioning
confidence: 99%
“…Recently, Miyata et al (2015) demonstrated that a sperm specific calcineurin is responsible for the transition that releases the ODFs during epididymal maturation of the sperm. Furthermore, they showed that specific inhibition of the process by calcineurin inhibitors renders the sperm of normal mice stiff in the midpiece.…”
Section: How the Sperm Tail Workmentioning
confidence: 99%